An Impact Review on the Performance of Civil Servants Following Local Government Budget Efficiency in Banda Aceh City - Endang Syahriani; Muhammad Ridha Ramli; Fitrian Rizky (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study seeks to explore and evaluate the impact of motivation, work discipline, and work stress on the performance of employees, with job satisfaction as a moderating variable, among Civil Servants in Banda Aceh City in the wake of the government’s regional budget efficiency policy. The budget efficiency policy implemented by the local government, as a response to fiscal constraints and economic dynamics, has various implications on the tasks and performance of Civil Servants. In Banda Aceh City, this policy represents a strategic step in optimizing resource management without compromising the quality of public services. However, reductions in operational budgets and employee expenditures may affect employee motivation, discipline, work stress, and job satisfaction in carrying out their duties. The population under study consists of employees from the Civil Servant category, which includes PNS and PPPK statuses, within Banda Aceh City. Accordingly, this study employs purposive sampling combined with incidental/convenience sampling methods. These sampling methods are chosen due to the convenience of selecting respondents when the total population size is unknown. Respondents are freely selected during the data collection period in June-July 2025. Data analysis was conducted using the Moderated Regression Analysis (MRA) method. The research results show that in the basic multiple linear regression model, work motivation and work discipline both have a significant impact on employee performance. However, work motivation is found to negatively influence employee performance. In the MRA model where job satisfaction acts as a moderating variable, work motivation and work stress exhibit a significant negative effect on employee performance, while work stress alone remains statistically insignificant. When job satisfaction moderates work motivation and work discipline, both variables positively and significantly influence employee performance. Conversely, work stress moderated by job satisfaction still does not have a significant effect on the performance of civil servants in Banda Aceh City, following the government's implementation of budget efficiency policies. Thus, human resource management in the Banda Aceh City government needs to prioritize job satisfaction as a central focus in efforts to improve employee performance under the budget efficiency policies introduced by the government. Programs aimed at increasing work motivation and work discipline will be more effective when accompanied by efforts to enhance job satisfaction through the development of a supportive work environment, provision of adequate rewards, and safeguarding the psychological well-being of employees—so that work stress can also be reduced.